IDEAL MARRIAGE IN HANUM SALSABILA RAIS AND RANGGA ALMAHENDRA’S NOVEL I AM SARAHZA - Lia Syafitri; Usman Sidabutar (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2020)
This study constituted an analysis of an ideal marriage in the novel published in 2018. The significant components of the marriage relationship found in the novel that could be categorized into an ideal marriage were the topics to discuss. One of the significant theories of an ideal marriage used in this study was A Triangular of Love that appears in three significant components: intimacy, passion and commitment that reflected the subjective experience. Intimacy could be considered the warm component because it encompassed the feeling of comfort and tenderness in a relationship. Then, passion consisted of motivational and was considered the hot component, in that it usually included the most intense feeling. Finally, commitment involved deliberate choice to love someone and to maintain that love. It was considered the cold component (Sternberg: 1986). The research was conducted by descriptive qualitative method. The research results showed that the three points of an ideal marriage in the novel, i.e. intimacy, passion, and commitment were clearly reflected by the major characters in the novel.